Research and the social work picture - Shaw, Ian 1945- (Policy Press, 2019)
There's a growing pressure for social workers to engage with research and draw on this in practice. But why is this research important? This first book in the Research in Social Work series, published in association with the European Social Work Research Association, provides an accessible way to think about this question. Drawing on evidence from across Europe, Asia and the USA, it covers how research is conducted, used, and perceived. It is perfect for social work students, researchers and practitioners, providing a detailed sketch of how research finds a place in the wider social work picture and offering opportunities and exercises that highlight how social work research is relevant in day-to-day course programmes and practice. The book will embolden a kind of scepticism, while at the same time providing the ground work for social workers to become more thoughtfully practical - and practically thoughtful. (Quelle: bristoluniversitypress.co.uk)
Keywords: Sozialarbeit; Forschung; Social service / Research